Geologia e Geomorfologia da Planície Costeira da Praia do Sul: Ilha Grande - Uma Contribuição à Elaboração do Plano Diretor da Reserva Biológica - Amador, Elmo da Silva (Anuário do Instituto de Geociências, 1987)
Based on stratigraphical, sedimentological and geomorphological methods, a preliminary stratigraphic division is proposed to the Praia do Sul coastal plain, a state Biological Reserve, located in "Ilha Grande", Rio de Janeiro. This reserve was created to preserve the natural ecosystems found therein (sandy coastal plain, mangrove, lagoon, rocky coast and hillside fo rest). The Praia do Sul sedimentation plain is essentially constituted by continental gravels and sands of Upper Pleistocene, marine sandy formations, fluvial-lagoonal sandy-clayer formations and present mangrove swamps and beachs. The paleogeographic evolution of this area can be followed through the sedimentary association that permits to establish the transgressive and regressive process that occured during the Quaternary period.